ULTRASOUND-GUIDED SALIVARY GLAND BOTULINUM TOXIN FOR CHRONIC SIALORRHEA IN OTOLARYNGOLOGY: PROCEDURAL TECHNOLOGY, SERVICE DELIVERY, AND PUBLIC HEALTH OUTCOMES - Daria Danielczyk; Michał Babicz; Kamil Chudzicki; Wiktor Czyżewski; Katarzyna Rosa; Agata Słoma; Anna Szot; Dominik Szydełko; Martyna Szymczyk; Paweł Żurek (International Journal of Innovative Technologies in Social Science, 2026)
Chronic sialorrhea has consequences that extend far beyond visible drooling. In otolaryngology practice it can affect airway protection, skin integrity, communication, feeding routines, social participation, school or work functioning, and unpaid caregiver time. This review synthesizes PubMed-indexed evidence on salivary gland botulinum toxin with particular attention to how imaging support, care setting, and service organization shape clinical and public-health outcomes. PubMed was used as the core database for a structured narrative search completed on March 12, 2026, and evidence was synthesized thematically, prioritizing randomized trials, systematic reviews, consensus documents, and larger cohort studies. Across adult and pediatric populations, botulinum toxin consistently reduces drooling severity in appropriately selected patients, while ultrasound guidance improves localization confidence and supports more reproducible, teachable protocols. The major unresolved questions concern optimal gland combinations, formulation-specific dose strategies, longer-term respiratory outcomes, comparative costs across settings, and equitable access for medically underserved populations. Current evidence supports botulinum toxin as a minimally invasive component of stepwise drooling management when paired with structured swallowing assessment, caregiver-centered outcomes, and implementation models that reduce avoidable anesthesia exposure and travel burden.